EBCOG position statement: Vaccination in pregnancy. (September 2019) - Benedetto, C.; Carosso, A.; Corezzi, M.; Zotti, C.M.; ,
Abstract: Maternal immunization has the potential to reduce morbidity and mortality from infectious diseases worldwide. EBCOG promotes this public health intervention supporting international recommendations about the use of vaccines during pregnancy.